An ultra-tunable platform for molecular engineering of high-performance crystalline porous materials - Quan-Guo Zhai (Nature Portfolio, 2016)
Synthetic design of crystalline porous materials is important for applications such as catalysis and adsorption. Here, the authors demonstrate a platform for the development of crystalline porous materials with a variety of organic ligands and metallic clusters, and control of their gas sorption properties.